2015
DOI: 10.1503/cjs.004214
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of the ankle syndesmosis

Abstract: Background: Radiographic measurements to document ankle anatomy have been suggested in recent literature to be inadequate. Focus has been put on stress views and computed tomography; however, there are also issues with these modalities. An orthogonal view that could be used both statically and dynamically could help determine syndesmotic stability. The purpose of this study was to determine a parameter on a normal lateral ankle radiograph that will increase the reliability of standard radiography in diagnosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Dikos et al [23] measured ATFI as 14.6±1.8 mm (11.0-19.4) on CT imaging. In the current study, the ATFI was measured as 12.8±2.4 mm (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and PTFI as 6.11 mm (3-15) on direct radiographs.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Dikos et al [23] measured ATFI as 14.6±1.8 mm (11.0-19.4) on CT imaging. In the current study, the ATFI was measured as 12.8±2.4 mm (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and PTFI as 6.11 mm (3-15) on direct radiographs.…”
Section: Discussionmentioning
confidence: 73%
“…Lateral measurements of ATFI and PTFI have been analyzed more commonly in CT imaging studies. [4,23] In studies by Croft et al, [13] it was reported that the ratio values were more reliable than millimetric measurements. Although the reliability of radiological measurements in CT imaging studies on sagittal planes is high, these values do not provide intraoperative direction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Grenier et al [ 32 ] have established a novel radiographic parameter based on the lateral view of the ankle, i.e., the anteroposterior tibiofibular (APTF) ratio, which is normally 0.94 ± 0.13 and can be used to identify and prevent a malreduction of the fibula in the incisura fibularis. Croft et al [ 33 ] showed that the anterior tibiofibular ratio (defined as the ratio of the tibial width to the anterior tibiofibular interval) is reproducibly measured, and is suitable for determining the normal relationship of the tibia and fibula. Some authors used CT to postoperatively evaluate the reduction of the injured syndesmosis [ 21 , 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements on lateral radiographs to assess the syndesmosis have not been well defined. Croft and colleagues 53 showed with high reliability that 40% of the tibia was anterior to the fibula at 1 cm above plafond. However, the rotation of the limb can significantly influence each of these measurements 54 except for the TFCS on the AP view.…”
Section: Initial Radiographic Evaluationmentioning
confidence: 98%